2020
DOI: 10.5530/jyp.2020.12.33
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pharmacist Intervention in the Management of Anemia Associated with Chronic Kidney Diseases at the Hemodialysis Setting

Abstract: Background:The potential impact of pharmacist interventions could improve health outcomes of patients with anemia. However, this attempt has not been documented yet in the developing countries. Aim of the study is to investigate the effect of pharmacist interventions in optimizing management of anemia associated with chronic kidney disease. Methods: An interventional randomized control trial was carried out on 120 anemic patients on hemodialysis for eight months. The impact of the pharmacist's interventions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The majority of short-listed articles were from the United States (n:5), 28 , 29 , 30 , 31 , 32 followed by two articles from Japan, 33 , 34 and the rest from Canada, 35 France, 36 Iraq, 37 Jordan, 38 Malaysia, 39 Nepal, 40 Peru, 41 Tanzania, 42 and Thailand. 43 The most common designs (n:6) used in the articles identified, were retrospective studies involving reviewing medication charts to evaluate the impact of pharmacists' roles in anaemia management.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of short-listed articles were from the United States (n:5), 28 , 29 , 30 , 31 , 32 followed by two articles from Japan, 33 , 34 and the rest from Canada, 35 France, 36 Iraq, 37 Jordan, 38 Malaysia, 39 Nepal, 40 Peru, 41 Tanzania, 42 and Thailand. 43 The most common designs (n:6) used in the articles identified, were retrospective studies involving reviewing medication charts to evaluate the impact of pharmacists' roles in anaemia management.…”
Section: Resultsmentioning
confidence: 99%
“…43 The most common designs (n:6) used in the articles identified, were retrospective studies involving reviewing medication charts to evaluate the impact of pharmacists' roles in anaemia management. 28 , 30 , 31 , 32 , 33 , 35 Three included studies that utilised randomised controlled trials to investigate the effect of pharmacists' interventions in anaemia management associated with chronic kidney disease, 37 among continuous ambulatory peritoneal disease patients, 39 and in iron deficiency anaemia. 38 Two articles utilised before-after design, one of the articles evaluating the impact of pharmacists after providing an educational training programme for patients, 36 and the other article was a pre-post evaluation of training implementation to support pharmacists in providing point-of-care testing, including anaemia.…”
Section: Resultsmentioning
confidence: 99%
“…Available studies reported the benefits and impact of pharmacy services in anaemia management. A study conducted showed that active participation of pharmacists in anaemia management significantly improved mean Hb level [8,16]. Other studies reported that pharmacist education program led to significant Hb improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In these locations, pharmaceutical services mainly include dispensing of medicines, patient education about their usage, management with psychotropic drugs, or control of medicine storage conditions. The impact of clinical pharmacy services on care of inpatients with CKD has yet to be established [ 26 , 31 , 32 , 34 , 36 , 55 ]. Therefore the proposed pharmacist-led interventions in these trials could deviate from real-world situations.…”
Section: Discussionmentioning
confidence: 99%